The Torsion with Bending Behaviour of a Tubular Truss - Okten, S.; Kasap, H. (Engineering Transactions, 1997)
In this study, elastic and elastic-plastic analysis of tubular square space trusses consisting of hollow bars has been carried out. The main purpose of the study is to obtain information useful in practice without making long calculations, and also to gain detailed information on the behaviour of the mentioned systems under torsion with bending in elastic and elastic-plastic region as well. In the elastic analysis, effects of variable span, existence of inner diagonals, different support conditions, vertical bar spacing and cross-sections on deflection, rotation and distortion are investigated. And, applying elastic-plastic analysis, it is examined how the effects mentioned above change the safety, ductility and the rotation capability of the truss.